Does the site of platelet sequestration predict the response to splenectomy in adult patients with immune thrombocytopenic purpura?. (September 2015) - Navez, Julie; Hubert, Catherine; Gigot, Jean-François; Navez, Benoit; Lambert, Catherine; Jamar, François; Danse, Etienne; Lannoy, Valérie; Jabbour, Nicolas
Abstract Splenectomy is the only potentially curative treatment for chronic immune thrombocytopenic purpura (ITP) in adults. However, one-third of the patients relapse without predictive factors identified. We evaluate the predictive value of the site of platelet sequestration on the response to splenectomy in patients with ITP. Eighty-two consecutive patients with ITP treated by splenectomy between 1992 and 2013 were retrospectively reviewed. Platelet sequestration site was studied by 111Indium-oxinate-labeled platelets in 93% of patients. Response to splenectomy was defined at last follow-up as: complete response (CR) for platelet count (PC) ≥100 × 109/L, response (R) for PC≥30 × 109/L and <100 × 109/L with absence of bleeding, no response (NR) for PC<30 × 103/L or significant bleeding. Laparoscopic splenectomy was performed in 81 patients (conversion rate of 16%), and open approach in one patient. Median follow-up was 57 months (range, 1–235). Platelet sequestration study was performed in 93% of patients: 50 patients (61%) exhibited splenic sequestration, 9 (11%) hepatic sequestration and 14 patients (17%) mixed sequestration. CR was obtained in 72% of patients, R in 25% and NR in 4% (two with splenic sequestration, one with hepatic sequestration). Preoperative PC, age at diagnosis, hepatic sequestration and male gender were significant for predicting CR in univariate analysis, but only age (HR = 1.025 by one-year increase, 95% CI [1.004–1.047], p = 0.020) and pre-operative PC (HR = 0.112 for > 100 versus <=100, 95% CI [0.025–0.493], p = 0.004) were significant predictors of recurrence-free survival in multivariate analysis. Response to splenectomy was independent of the site of platelet sequestration in patients with ITP. Pre-operative platelet sequestration study in these patients cannot be recommended.